Second-Graders' Understanding of Comparison Tasks - Маrijana Ž. Zeljić; Мilana M. Dabić Boričić; Svetlana M. Ilić (University of Belgrade, Teacher Education Faculty, 2023)
The paper examines students' understanding of relational terminology and their achievement in solving comparison tasks identified in the existing literature as the most difficult among the tasks with a single calculation operation. We expand previous research by examining achievement on more complex tasks in which comparison problems are subproblems within the combining problem; by examining students' achievement on tasks with two comparisons, and examining the effect of consistency on the tasks of different semantic structure. The research results indicate that the consistency effect, which is reflected in the use of the wrong operation due to the misunderstanding of the relational terminology, was the dominant problem for students when solving comparison tasks. The number of comparisons in the task, as well as the semantic structure of the problem, did not prove to be significant factors affecting students' success. In addition, the existence of a moderate connection between consistent and inconsistent formulations exists only on tasks with a more complex structure. The results indicate that it is possible only on the tasks with a more complex structure to determine whether students demonstrate a deeper understanding of the comparison tasks. Conceptual understanding of comparison problems is built through understanding more/less relations and the use of the tasks of different semantic structures and complexity.